Modifications to Implanting the OSIA® 2 Bone Conduction Hearing Implant: How I Do it. (26th May 2022) - Deep, Nicholas L.; Johnson, Brian J.; Kay‐Rivest, Emily; Carlson, Matthew L.; Friedmann, David R; Driscoll, Colin L.W.; Thomas Roland, J.; Jethanamest, Daniel
Abstract : This "How I Do It" report describes modifications made to the OSIA bone conduction hearing implant surgery in order to reduce wound complications. Laryngoscope, 132:1850–1854, 2022